(untitled) (American Journal of Islam and Society, 2001)
This essay shows how the concept of womanhood undergoes a transformation in the minds of some western females who convert to the Muslim faith. With respect to the role of women in Islam, three different groups may be distinguished: “outsiders looking in,” “insiders looking out;” and “converts to Islam looking around and back.” Within the first category, a majority see Islam in terms of oppression and servitude, although for a smaller group the faith represents a return to all that “hearth and home” signifies. The second major grouping consists of Muslims, many of whom find Muslim womanhood to be superior to non-Islamic alternatives. But an increasing number seek to liberate females from “the tyranny of Islamic Law.” Those in the third category were originally “outsiders looking in,” but after a transitional period become “insiders looking out.” The . female converts are originally attracted to a feminine ideal that is interpreted through their own culture and experience. Becoming “insiders” brings exposure to issues of Islamic womanhood which necessitate a re-interpretation of the essence of femaleness, producing what uninitiated western observers might call rationalizations but which actually form apologetical replies to objections from unbelievers.